What the Native Americans wore - Williams, Colleen Madonna Flood (Native American life, 2003)
An examination of Native American life, discussing the different types of clothing worn by various tribes, and looking at the cultural or religious significance of certain articles of clothing, jewelry, and other adornments. Includes a chronology and glossary.